Effects of heating and calcium and phosphate mineral supplementation on the physical properties of rennet-induced coagulation of camel and cow milk gels. Issue 2 (19th May 2017) - Kamal, Mohammad; Foukani, Mohammed; Karoui, Romdhane
Abstract : The physical properties of rennet-induced coagulation of preheated camel and cow milk gels (50 and 70 °C for 10 min) enriched with calcium chloride (CaCl2 ) and hydrogen phosphate dihydrate (Na2 HPO4 2H2 O) were evaluated using the dynamic low amplitude oscillatory shear analysis. The storage modulus ( G ʹ) and loss modulus ( G ʺ) of camel milk gels showed significant ( P < 0·05) lower values than those of cow milk gels. The preheating of camel milk at 50 °C affected negatively the gelation properties, while the preheating at 70 °C prevented the formation of rennet-induced milk gels. No effect was observed on the gelation properties of cow milk gels. The CaCl2 added at 10 and 20 mM to preheated camel and cow milk reduced significantly ( P < 0·05) the gelation time and increased the gel firmness. In contrast, Na2 HPO4 2H2 O added at 10 and 20 mM induced the formation of weak gels for preheated camel and cow milk at 50 °C, and even no gelation for preheated camel milk at 70 °C.